LOW-COST PROTOTYPES WITH SOLAR THERMAL UTILIZATION - Díaz, Andrés Emanuel; Di Lalla, Nicolás; Hernández, Alejandro Luis (Journal of Advance Research in Food, Agriculture and Environmental Science (ISSN 2208-2417), 2025)
This paper presents the construction of five solar thermal utilization devices: two food dryers, a solar water heater, a solar water distiller, and a solar food cooker. These devices were built under the direction and supervision of the authors of the article by students enrolled in the semester course "Materials and Construction of Solar Equipment" in the final year of the "Technical Degree in Solar Energy" at the National University of Salta. The devices were made with the premise of using recycled materials and low-cost techniques. While the prototypes developed are demonstrative and of medium scale, they are fully operational and functional. The results were satisfactory, as the reductions in the initial masses of the products dried by the prototypes were around 90%, the solar cooker reached 80ºC on days with low solar radiation, the outlet water temperature of the solar water heater reached 58ºC, and the solar distiller produced 500 ml daily with a conductivity of 68 µS/cm.